1998
DOI: 10.1055/s-2007-995853
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Tissue-Type Plasminogen Activator Receptor (t-PAR) in Human Endothelial Cells

Abstract: Vascular endothelial cells regulate the fibrinolytic system in blood by expressing cell-surface receptors for plasminogen and plasminogen activators (PAs) as well as secreting PAs and their inhibitors. Although several receptors for plasminogen and PAs have been identified in many cell types, little is known about tissue-type PA (t-PA)-specific receptor (t-PAR) on endothelial cells except a few reports. By using suspended human umbilical vein endothelial cells (HUVEC), which are free from the formation of extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2000
2000
2003
2003

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
1
1
Order By: Relevance
“…Several previous studies have suggested the presence of tPA binding protein on the cell surface that might serve as a docking receptor for tPA (Pittman et al, 1989;Verrall and Seeds, 1989;Hajjar et al, 1994;Fukao and Matsuo, 1998). However, our current study suggests that tPA is rapidly endocytosed by LRP after its binding to the receptor, suggesting that LRP likely functions as an endocytosis/signaling receptor as opposed to a docking receptor.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Several previous studies have suggested the presence of tPA binding protein on the cell surface that might serve as a docking receptor for tPA (Pittman et al, 1989;Verrall and Seeds, 1989;Hajjar et al, 1994;Fukao and Matsuo, 1998). However, our current study suggests that tPA is rapidly endocytosed by LRP after its binding to the receptor, suggesting that LRP likely functions as an endocytosis/signaling receptor as opposed to a docking receptor.…”
Section: Discussioncontrasting
confidence: 60%
“…Both LRP and a mannose receptor have been shown to bind tPA (Otter et al, 1991;Bu et al, 1992b). In addition, several studies have described various tPA binding receptors on the cell surface of both endothelial and neuronal cells (Pittman et al, 1989;Verrall and Seeds, 1989;Hajjar et al, 1994;Fukao and Matsuo, 1998). However, only binding to LRP is inhibited by RAP (Bu et al, 1998).…”
Section: Resultsmentioning
confidence: 99%